Rechargeable Lithium Metal Batteries with an In‐Built Solid‐State Polymer Electrolyte and a High Voltage/Loading Ni‐Rich Layered Cathode - Zhao, Chen‐Zi; Zhao, Qing; Liu, Xiaotun; Zheng, Jingxu; Stalin, Sanjuna; Zhang, Qiang; Archer, Lynden A. (Advanced materials (Weinheim), 2020)
Solid‐state batteries enabled by solid‐state polymer electrolytes (SPEs) are under active consideration for their promise as cost‐effective platforms that simultaneously support high‐energy and safe electrochemical energy storage. The limited oxidative stability and poor interfacial charge transport in conventional polymer electrolytes are well known, but difficult challenges must be addressed if high‐voltage intercalating cathodes are to be used in such batteries. Here, ether‐based electrolytes are in situ polymerized by a ring‐opening reaction in the presence of aluminum fluoride (AlF3) to create SPEs inside LiNi0.6Co0.2 Mn0.2O2 (NCM) || Li batteries that are able to overcome both challenges. AlF3 plays a dual role as a Lewis acid catalyst and for the building of fluoridized cathode–electrolyte interphases, protecting both the electrolyte and aluminum current collector from degradation reactions. The solid‐state NCM || Li metal batteries exhibit enhanced specific capacity of 153 mAh g−1 under high areal capacity of 3.0 mAh cm−2. This work offers an important pathway toward solid‐state polymer electrolytes for high‐voltage solid‐state batteries. Solid‐state batteries are under active consideration for their promise as cost‐effective platforms that simultaneously support high‐energy and safe electrochemical energy storage. In this work, ether‐based solid‐state polymer electrolytes are created inside a battery using ring‐opening polymerization in the presence of aluminum fluoride (AlF3). The electrolytes are shown to mitigate cathode corrosion and to enable solid‐state LiNi0.6Co0.2 Mn0.2O2 (NCM)||Li batteries with high capacities.